Visão além do alcance: práticas de uso e disciplina Tecnossensorial do Drone - Fleischmann, Damean Klaus de Castro (Universidade do Vale do Rio dos Sinos, 2019)
What are the concrete uses of drones in the immediate lived space? Is there no relation of affectation and convergence between the drone of war culture and that of civilians? Are we facing a new need, the emergence of a new visual and behavioral culture? Through these doubts, we urge the reader to reflect on the possibilities that are "hidden" when using this technology, and that have been building in the last 10 years, in Brazil, not only new businesses, but contributing to the transformation of communication. We applied an exploratory research followed by techniques of observation, interview and analysis of records. And from these, we draw a comparison between cultures, in order to understand the relationship of the actors-drones-cameras actors, precisely to identify similarities and dissimilarities, trends stimulated by digital effects of vision and expressive relationship with technology. We drew a line of thought about field collection based on Paul Virilio's Machine Vision, War & Cinema, and Gregoire Chamayou's Drone Theory, to understand the phenomenon of social relation with communication technology. As a result, we identify the sum of feeling, need, expression, sharing of "intelligence" and sensory experience, digital effects of images, principle of the emergence of an immersive social network and the beginning of the new generation of "warriors" state of modern warfare. All this as a result of the exploitation of a remotely controlled media.
Keywords: Drone; Câmera; Culturas; Visão; Transformação; Tecnossensorial; Drone; Camera; Cultures; View; Transformation; Technosensorial; ACCNPQ::Ciências Sociais Aplicadas::Comunicação